The Nuremberg Code and the individual’s autonomy - Krzyżewska, Barbara (Studia Ecologiae et Bioethicae, 2016)
The article shows how important and necessary are the principles established by a judgment of one of the Nuremberg Trials. It also shows an emanation of these rules in two areas: in law and in ethics. The text also reveals how close to each other are those areas, when we talk about the medical law. The work focuses on the autonomy of the patient and the prerequisites on which the consent to a medical experiment is valid.